Wczesna opieka logopedyczna nad dzieckiem z rozszczepem wargi i podniebienia. Standard postępowania logopedycznego przyjęty w Instytucie Matki i Dziecka w Warszawie - Radkowska, Elżbieta (Logopedia Silesiana, 2015)
The child born with cleft lip and palate requires multidisciplinary care since the very first hours of its life. These actions should also include speech therapy stimulation. Initially, the work of a speech therapist over dealing with this birth defect differs from the standard therapeutic procedures as a speech therapist comes into contact with a very young patient who has difficulties with food intake and often suffers from swallowing and breathing disorders.This study contains a proposal for speech therapy care over a child with cleft lip and palate. The method is used in the clinics of the Mother and Child Institute in Warsaw.